Evapotranspiration and yield of off-season maize and crotalaria intercropped - Daniel, Diego Fernando (2020)
Intercrop systems come as an alternative to reduce soil water evaporation and consequently greater availability of water for plants. This study aimed to verify the influence of the intercrop between the maize crop and the crotalaria, determining the crop evapotranspiration and evaluating the effect of water competition on the productive characteristics of the maize crop. The experiment was carried out in the experimental field of the Mato Grosso State University (UNEMAT), consisting of three treatments: T1 - single maize (Zea mays L.), T2 - single crotalaria (Crotalaria juncea L.), and T3 - maize and crotalaria intercrop. Reference evapotranspiration (ETo) was estimated using the methodology proposed by Penman-Monteith FAO-56. The crop evapotranspiration (ETc) of the treatments were determined daily by varying the weight of weighing lysimeters, converted into mm day-1. Soil evaporation was determined using microlysimeters. The phenological phases of the cultures were determined for the determination of ETc in the different stages of development as recommended by FAO-56, being: Initial (I), Development (II), Intermediate (III), and Final (IV). The components of maize productivity were evaluated at the end of the crop cycle. Soil evaporation was reduced by 43.91 mm (26.78%), and transpiration was reduced by 19.64 mm (14.85%) when using the intercropped maize system, in relation to maize in single cultivation. The accumulated ETc was 312.00; 436.16 and 422.38 mm, for maize, crotalaria and intercropping, respectively. Yield was 6739.26 and 4571.85 kg ha-1, for single and intercropped maize, respectively.